Study abroad perspectives and experiences from business schools - Hult, G. Tomas M.; Lashbrooke, E. C. (JAI Imprint, 2003)
Business educators everywhere are looking for opportunities where students can gain experiences through study or work in an international context. Study abroad offers meaningful opportunities for exposing business students to cross-cultural learning. In this volume, experts share experiences and guidelines for initiating study abroad programs in business schools. A variety of key issues are discussed, including funding for study abroad fellowships, integrating foreign language training, administrative arrangements for study abroad, and best practices. Perspectives from both US and European business schools are addressed.
Selected papers from the Roundtable on Study Abroad Programs in Business Schools, held Sept. 2001 at East Lansing, Mich.
Keywords: Business education -- Congresses.; Business schools -- Congresses.; Foreign study -- Congresses.; American students -- Foreign countries -- Congresses.; elektronické knihy; electronic books